2009
DOI: 10.1200/jco.2008.20.6870
|View full text |Cite
|
Sign up to set email alerts
|

Two-Center Evaluation of Dynamic Sentinel Node Biopsy for Squamous Cell Carcinoma of the Penis

Abstract: Sentinel node biopsy is a suitable procedure to stage clinically node-negative penile cancer, and it has a low complication rate. No learning curve was demonstrated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(74 citation statements)
references
References 29 publications
(1 reference statement)
8
60
5
1
Order By: Relevance
“…A recent study [5] reported a rate of seroma of 9.7%, more than one-half of which required aspiration (5.7%) (n = 139). In a single-site study evaluating outcomes following SLNB for penile cancer, rate of surgical site infection and abscess was 4% and seroma was 2%, which was similar to a multi-center study that demonstrated an infection rate of 3% and a seroma rate of 3.1% [7]. It is notable that rates of complications are significantly lower in retrospective studies, with overall complication rates reported from < 1% to 2% [8,9].…”
mentioning
confidence: 56%
“…A recent study [5] reported a rate of seroma of 9.7%, more than one-half of which required aspiration (5.7%) (n = 139). In a single-site study evaluating outcomes following SLNB for penile cancer, rate of surgical site infection and abscess was 4% and seroma was 2%, which was similar to a multi-center study that demonstrated an infection rate of 3% and a seroma rate of 3.1% [7]. It is notable that rates of complications are significantly lower in retrospective studies, with overall complication rates reported from < 1% to 2% [8,9].…”
mentioning
confidence: 56%
“…Nowadays, more and more penile cancer patients with clinical negative lymph nodes were subjected to less invasive staging procedures such as sentinel nodal biopsy, and superficial or modified dissection . [21,[45][46][47][48][49] . Regardless the metastases deposit, extensive dissection is performed if one positive lymph node is found.…”
Section: N0mentioning
confidence: 99%
“…Patients with sentinel lymph node positive disease are still lack of valuable prognostic factors to stratify long-term outcome. Regionalization of penile cancer care and international collaboration, as adopted by European colleagues [45] , will allow investigators to overcome these drawbacks and perform well designed studies.…”
Section: N0mentioning
confidence: 99%
“…The patient and recurrent tumour characteristics are presented in Table 1. The results of the primary dynamic SNB of these patients were included in a previously reported series [7].…”
Section: Methodsmentioning
confidence: 99%
“…The latter causes substantial short-and long-term complications [3]. This is avoided with dynamic SNB [4], a minimally invasive staging technique for patients with clinically normal lymph nodes [5][6][7]. Inguinal node dissection is done only if the sentinel node is tumourpositive.…”
Section: Introductionmentioning
confidence: 99%